The Impact of Transportation Infrastructure on Green Total Factor Productivity - Chen, Haonan (International Journal of Social Sciences and Public Administration, 2025)
This study examines the effect of transportation infrastructure on Green Total Factor Productivity (GTFP) across 50 countries from 2001 to 2021. Using a non-radial, non-oriented Slacks-Based Measure (SBM) to measure GTFP and explores the impact of infrastructure development. Results show that transportation infrastructure positively contributes to GTFP. Other key factors, including foreign direct investment (FDI), urbanization, government intervention, and R&D investment, also significantly influence GTFP. The findings suggest that tailored infrastructure and policies are crucial for maximizing green development.